Perencanaan Manajemen Sumber Daya Manusia pada Bisnis Plan Laboratorium Klinik Colostat Test - Melni Rohana; Tantri Yanuar Rahmat Syah; Edi Hamdi; Muhammad Reza Hilmy (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
PT Mekogene Indonesia (PT MGI) business planning focuses on the innovation of a blood test-based colorectal cancer screening tool, ColoSTAT. ColoSTAT is indicated to be able to screen the risk of colorectal cancer in adult colorectal cancer suspects aged 40-85 years. PT MGI's external environmental analysis uses PESTEL and Porter's Five Forces. This research method uses literature studies and interviews with related parties. The analysis shows that the increasing trend in colorectal cancer rates, support for health regulations, and public awareness open up large market opportunities. However, there are challenges such as competition from conventional technology and challenges in educating the public about the importance of early detection. The strengths of this medical device market include high barriers to entry, low consumer bargaining power, and the potential for market dominance through technological innovation. PT MGI's human resource (HR) development planning includes a lean but effective organizational structure, a modern diagnostic technology training program, and a performance-based compensation system to increase productivity. The core team will consist of experts in diagnostic technology and market development.